2010
DOI: 10.1002/adma.201003759
|View full text |Cite
|
Sign up to set email alerts
|

Sandwich‐Like, Stacked Ultrathin Titanate Nanosheets for Ultrafast Lithium Storage

Abstract: Nanomaterials in architecture for green energy conversion and/ or storage provide one of the most desirable approaches to alleviate environmental and energy issues. [1][2][3][4] As a result, there is increasing interest in developing high-power anode materials, which can match with the state-of-the-art high-power cathode materials, for next generation high-performance rechargeable Li-ion batteries. [5][6][7] Titanium dioxide is regarded as one of the ideal candidates for high-rate anode materials, owing not on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
144
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 211 publications
(150 citation statements)
references
References 40 publications
6
144
0
Order By: Relevance
“…This capacity loss is relatively low compared to those in previous reports, in which nanostructured electrode materials or low temperaturetreated TiO 2 materials show a fi rst irreversible capacity loss of 20%−40%. [ 2,48 ] One possible reason to the fi rst-cycle capacity loss is presented as follows. The annealing of hydrogen titanate at 550 °C did not completely eliminate the surface impurities.…”
Section: Lithium-ion Battery Propertiesmentioning
confidence: 99%
“…This capacity loss is relatively low compared to those in previous reports, in which nanostructured electrode materials or low temperaturetreated TiO 2 materials show a fi rst irreversible capacity loss of 20%−40%. [ 2,48 ] One possible reason to the fi rst-cycle capacity loss is presented as follows. The annealing of hydrogen titanate at 550 °C did not completely eliminate the surface impurities.…”
Section: Lithium-ion Battery Propertiesmentioning
confidence: 99%
“…This phenomenon is similar to that reported for nanostructured titania with high capacity, in which an additional surface lithium storage mechanism exists. [ 11 ] Thereby, such surface lithium storage combined with the classic interlayer storage gives rise to a high capacity of 202 mAh g − 1 for G-TiO 2 nanosheets during the initial charging process. Although this value is almost the same as that of TiO 2 nanosheets without graphene at the fi rst cycle (Figure S4), the capacity loss between G-TiO 2 and TiO 2 becomes large as the cycle number is increased (Figure 4 c), demonstrating that the graphene layers in titania nanosheets play an essential role for the improvement of the cycle performance.…”
Section: Doi: 101002/adma201101599mentioning
confidence: 99%
“…[35] Moreover, it is highly possible for organic species to intercalate into the interlayer spacing of the layered structure. [39] We further investigated the effects of synthesis parameters on the structure of the LTHSs. It was found that the size and morphology of LTHSs are tunable by controlling Scheme 1.…”
mentioning
confidence: 99%